Inward dispersion of the spin excitation spectrum of stripe-ordered La2NiO4+d - Freeman, P; Hayden, S; Frost, C; Enderle, M; Yao, D; Carlson, E; Prabhakaran, D; Boothroyd, A (2009)
Polarized- and unpolarized-neutron scattering measurements of the spin excitation spectrum in the stripe-ordered phase of La2NiO4+d (d = 0.11) are presented. At low energies, the magnetic spectral weight is found to shift anomalously towards the two-dimensional antiferromagnetic wave vector, similar to the low-energy dispersions observed in cuprate superconductors. While spin-wave spectra in stripe phases can exhibit an apparent inward dispersion, we find that the peak shifts measured here cannot be accounted for by this effect. Possible extensions of the model are discussed.